Data and Information Activities of ICSWSE, Kyushu University, Japan - Shuji Abe; Kiyohumi Yumoto; Akihiro Ikeda; Teiji Uozumi; George Maeda (Data Science Journal, 2013)
In this paper, we introduce data and information activities of the International Center for Space Weather Science and Education (ICSWSE), Kyushu University, Japan. The principal data source is the MAGDAS (MAGnetic Data Acquisition System) project, which is a global network of geomagnetic observations operated by collaborations between ICSWSE and institutions in many countries. We operate 66 stations including more than 30 stations distributed along the 210o magnetic meridian and more than 10 stations along the magnetic equator. We have established a semi-automatic data acquisition system via the Internet. Provisional data plots and geomagnetic indices derived from the project are available to the scientific community.